Ocular Manifestations of HIV And Aids - Dr.Anandakakumar,M.S, Dr.B.V.Satyanarayana, M.S, (International Journal of Scientific Research and Management (IJSRM), 2015)
The role of Ophthalmologist in the diagnosis and management of AIDS is becoming increasingly important .Not only thus the eye reflect systematic disease but ocular involvement may proceed systemic manifestations .The eye is the most common organ affected due to AIDS .Ocular involvement in AIDS is about 50-70%.Ocular lesions are varied and affect almost all structures of the eye.